Rediscovering black phosphorus as an anisotropic layered material for optoelectronics and electronics - Xia, Fengnian; Wang, Han; Jia, Yichen (Nature communications, 2014)
Graphene and transition metal dichalcogenides (TMDCs) are the two major types of layered materials under intensive investigation. However, the zero-bandgap nature of graphene and the relatively low mobility in TMDCs limit their applications. Here we reintroduce black phosphorus (BP), the most stable allotrope of phosphorus with strong intrinsic in-plane anisotropy, to the layered-material family. For 15-nm-thick BP, we measure a Hall mobility of 1,000 and 600 cm 2 V −1 s −1 for holes along the light ( x ) and heavy ( y ) effective mass directions at 120 K. BP thin films also exhibit large and anisotropic in-plane optical conductivity from 2 to 5 μm. Field-effect transistors using 5 nm BP along x direction exhibit an on–off current ratio exceeding 10 5 , a field-effect mobility of 205 cm 2 V −1 s −1 , and good current saturation characteristics all at room temperature. BP shows great potential for thin-film electronics, infrared optoelectronics and novel devices in which anisotropic properties are desirable. The applications of graphene and transition metal dichalcogenides in electronics are limited by their zero-bandgap and low mobility, respectively. Here, the authors demonstrate the potential of an emerging layered material—black phosphorous—for thin film electronics and infrared optoelectronics.